Determinants of Generation Z Tourist Satisfaction at Museum Sonobudoyo - Setiawan, Wahyu; Azizah, Nur (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This study aims to analyze the influence of promotion, price, and service quality on the satisfaction of Generation Z tourists at Museum Sonobudoyo, Yogyakarta. A quantitative approach was employed, with data collected through questionnaires distributed to 150 respondents from Generation Z (born between 1997–2012) who had visited Museum Sonobudoyo at least once in the preceding six months. Purposive sampling was used, and data were analyzed using multiple linear regression. The results indicate that promotion, price, and service quality each exert a positive and significant influence on Generation Z tourist satisfaction. These findings imply that authentic digital promotional strategies, affordable and transparent pricing, and adaptive service quality constitute an effective combination for enhancing the satisfaction of younger tourists at cultural tourism destinations